2003
DOI: 10.1091/mbc.e02-10-0700
|View full text |Cite
|
Sign up to set email alerts
|

Irod/Ian5: An Inhibitor of γ-Radiation- and Okadaic Acid-induced Apoptosis

Abstract: Protein phosphatase-directed toxins such as okadaic acid (OA) are general apoptosis inducers. We show that a protein (inhibitor of radiation- and OA-induced apoptosis, Irod/Ian5), belonging to the family of immune-associated nucleotide binding proteins, protected Jurkat T-cells against OA- and γ-radiation-induced apoptosis. Unlike previously described antiapoptotic proteins Irod/Ian5 did not protect against anti-Fas, tumor necrosis factor-α, staurosporine, UV-light, or a number of chemotherapeutic drugs. Irod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 76 publications
2
80
0
1
Order By: Relevance
“…We also found this localization to be dependent on the presence of the hydrophobic transmembrane domain. In a recent publication by Sandal et al, 14 IROD/ Ian5 (which is identical to hIAN5) was shown to be localized in the centrosomal/Golgi/ER compartment, and the removal of the C-terminal domain caused no defect in the antiapoptotic function of IROD, but led to a decrease in Golgi and ER localization of IROD. In their experiment, they expressed an HA-Ian5-GFP protein in order to determine Ian5 localization.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We also found this localization to be dependent on the presence of the hydrophobic transmembrane domain. In a recent publication by Sandal et al, 14 IROD/ Ian5 (which is identical to hIAN5) was shown to be localized in the centrosomal/Golgi/ER compartment, and the removal of the C-terminal domain caused no defect in the antiapoptotic function of IROD, but led to a decrease in Golgi and ER localization of IROD. In their experiment, they expressed an HA-Ian5-GFP protein in order to determine Ian5 localization.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the GDP/GTP-binding domain was not necessary for this effect, and a very small fragment including the coiled-coiled domain was sufficient for mediating this effect. 14 Taken together, the investigation of the function of Ian family members suggests that Ian proteins are a distinct group of GTP-binding proteins that play a role in immune responses (plant: hypersensitivity; mammals: thymocyte development (autoimmunity)) and are involved in the control of lymphocyte apoptosis (lymphopenia). 4,6,7,[9][10][11][12][13][14] Here we describe the characterization of hIan5, the human ortholog to rIan4/Iddm1/lyp.…”
Section: Introductionmentioning
confidence: 99%
“…Bar 5 mm for all panels except (b) and (f), where it is 0.5 mM may explain why ROS-inducing gamma irradiation and okadaic acid both lead to CaMKII-dependent Jurkat cell apoptosis. 3 The MC-induced death had two stages. The first stage was characterized by polarized budding, and pronounced shrinkage with apparently intact DNA and mitochondria (Table 1, Figures 1 and 8).…”
Section: Discussionmentioning
confidence: 99%
“…One way in which this can happen is by PP inhibitors short-circuiting an apoptogenic cell stress pathway induced by ionizing radiation. 3 We reported early that the PP-inhibiting toxins induced morphological alterations compatible with apoptosis in a number of cell types. 4,5 It was also found early that okadaic acid and microcystin could alter the cytoskeleton of fibroblasts and hepatocytes without inducing death.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of ␥ tubulin mislocalization from centrosomes and induction of apoptosis through DAPlike kinase has not been explored. Mislocalization of survivin and other antiapoptotic proteins from centrosomes can induce apoptosis (Reed and Reed, 1999;Piekorz et al, 2002;Sandal et al, 2003). Additional studies will be required to identify the proteins and pathways involved in the apoptotic response observed after disruption of the pericentrin-GCP2/3 interaction.…”
Section: G2/antephase Delay and Apoptosismentioning
confidence: 99%